Highly abrasion-resistant post-granulation cylindrical activated carbon and preparation process thereof

CN122977376APending Publication Date: 2026-10-27FUJIAN XINSEN CARBON +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611433721.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

聚乙烯醇粘结剂耐热性差,长期处于200℃以上高温环境会发生分子链断裂、热解失效,最终成品机械强度、耐磨性能偏低;同时含原生木质组分的生坯直接高温炭化活化,原料内氢、氧等非碳元素快速大量析出挥发分,叠加热胀冷缩效应,物料产生不均匀收缩、内部集中应力,导致活性炭颗粒变形、开裂,尺寸一致性差,成品合格率低

Benefits of technology

[0032]1、本发明通过先活化、后造粒低温成型主线,将硅烷偶联改性、有机交联粘结体系适配至低温后造粒工艺。本发明粘结剂体系全程所处最高烘干温度仅为130℃,硅烷、聚乙烯醇、木质素交联结构完整不发生热分解,能够长期稳定保障颗粒粘结强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977376A_ABST
    Figure CN122977376A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of activated carbon preparation, and discloses high-wear-resistance post-granulation columnar activated carbon and a preparation process thereof. The process comprises the following steps: preparing wood activated carbon powder through phosphoric acid activation, and carrying out surface hydroxyl pretreatment on the wood activated carbon powder through citric acid; preparing composite bonding glue containing polyvinyl alcohol, modified alkali lignin, low-molecular-weight urea-formaldehyde resin, silane coupling agent, nano fumed silica and the like; mixing the carbon powder with the glue, and then carrying out hydraulic extrusion molding, and then carrying out step-by-step low-temperature drying and natural particle breaking and screening to obtain a finished product. The application adopts the method of activating first and granulating later and low-temperature molding throughout the process, avoids high-temperature damage to the binder and the pore structure, simultaneously improves the butane working capacity and the wear resistance through silane molecular bridging, organic crosslinking network and nano fumed silica pore protection, and is suitable for harsh scenes such as automobile carbon tanks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of activated carbon preparation technology, specifically to a highly wear-resistant granulated columnar activated carbon and its preparation process. Background Technology

[0002] When a gasoline-powered vehicle is in motion or parked, the fuel tank continuously releases gasoline vapor. The charcoal canister relies on its internal columnar activated carbon to adsorb the gasoline vapor, which is then desorbed and sent to the engine for combustion, thereby controlling the emission of fuel vapor pollutants. GB18352.6-2016 significantly tightened the fuel vapor emission standards, requiring that the activated carbon filled in the charcoal canister possess both high butane working capacity and high wear resistance. However, existing manufacturing processes generally suffer from an inherent contradiction where adsorption capacity and wear resistance are mutually exclusive.

[0003] The current mainstream pre-granulation phosphoric acid method for columnar activated carbon involves mixing wood powder such as peach shells and walnut shells with a polyvinyl alcohol binder, extruding the mixture, and then subjecting it to prolonged hardening and high-temperature activation. However, the polyvinyl alcohol binder has poor heat resistance; prolonged exposure to temperatures above 200°C causes molecular chain breakage and pyrolysis, resulting in low mechanical strength and wear resistance in the final product. Furthermore, the direct high-temperature carbonization and activation of the green body containing virgin wood components leads to the rapid and large-scale release of non-carbon elements such as hydrogen and oxygen from the raw material. Combined with the thermal expansion and contraction effect, this causes uneven shrinkage and internal stress concentration in the material, resulting in deformation and cracking of the activated carbon particles, poor dimensional consistency, and a low finished product yield.

[0004] In view of this, the applicant conducted in-depth research on the above-mentioned issues, which led to this case. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a highly wear-resistant granulated columnar activated carbon and its preparation process, which can effectively solve the aforementioned technical problems.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A process for preparing post-granulated columnar activated carbon, characterized by comprising the following steps:

[0008] Step S1: Phosphoric acid activation to prepare wood-based activated carbon powder

[0009] (1) Raw material mixing: Walnut shell powder and sawdust are mixed at a mass ratio of 0.2:0.8 and sieved through a 40-60 mesh screen; Phosphoric acid aqueous solution and mixed wood powder are added to a kneader at a mass ratio of 1.4-1.5:1 and mixed evenly. The mixture is then cured at a constant temperature of 150℃ for 60 minutes to obtain the cured material.

[0010] (2) Hardening and shaping: The cured material is placed in a constant temperature environment of 180-200℃ for 16-20h to harden, and phosphoric acid cross-links with wood fiber to form a stable carbon-phosphorus composite skeleton;

[0011] (3) Inert atmosphere activation: Hardened carbon is activated at 450-480℃ for 0.5-1h under nitrogen protection atmosphere, and the nitrogen flow rate is controlled at 0.8-1.5m³ / h per 100kg of hardened carbon; Phosphoric acid is decomposed by heat and etches the carbon skeleton, generating a hierarchical porous structure in situ;

[0012] (4) Washing and drying: The activated carbon is repeatedly rinsed with hot water until the pH of the material is 6, and then completely dried at 120℃ to remove moisture;

[0013] (5) Ball milling: The dried activated carbon is ball milled to 325-400 mesh to obtain basic activated carbon powder;

[0014] (6) hydroxyl pretreatment of carbon powder surface: Activated carbon powder is immersed in 0.5% citric acid aqueous solution at room temperature for 30 min, filtered, rinsed with water to remove free acid on the surface, and dried at 80℃ for later use.

[0015] Step S2: Preparation of silane-modified lignin composite adhesive

[0016] Based on the total mass of activated carbon powder, the following amounts of each component of the adhesive were added: 3%–7% polyvinyl alcohol (PVA1799), 2%–4% modified alkali lignin, 1%–2% low molecular weight urea-formaldehyde resin, 0.1%–0.5% 3-aminopropyltriethoxysilane (KH-550), 0.1%–0.3% cocamidopropyl betaine, 0.2%–0.8% nano-fumed silica, with the remainder being deionized water;

[0017] The modified alkali lignin has a weight-average molecular weight of 8000–12000 and a phenolic hydroxyl content ≥3.2 mmol / g; the low molecular weight urea-formaldehyde resin has a solid content of 48%–52% and a free aldehyde content ≤0.3%.

[0018] The preparation steps of the adhesive solution include:

[0019] (1) Heat deionized water to 85-90℃, slowly add polyvinyl alcohol, keep warm and stir for 2 hours until completely dissolved;

[0020] (2) The system was cooled to 70°C, and 3-aminopropyltriethoxysilane diluted with pure water was slowly added dropwise to the polyvinyl alcohol solution. The crosslinking reaction was carried out at the temperature for 1 hour to form a silane-modified polyvinyl alcohol base solution.

[0021] (3) Pre-disperse nano-fumed silica with warm water accounting for 10% of the total water volume and cocamidopropyl betaine at high speed for 10 min to form a uniform dispersion;

[0022] (4) Add the dispersion, modified alkali lignin and low molecular weight urea-formaldehyde resin to the base liquid in sequence, stir continuously until uniform, and keep warm at 60°C for 1.5h to obtain a uniform and stable composite adhesive. The adhesive should be used within 24 hours after preparation and the storage temperature should be controlled below 40°C.

[0023] Step S3: Mixing and Hydraulic Extrusion Molding

[0024] (1) Add water to the pretreated activated carbon powder and stir for 3-5 minutes to eliminate the electrostatic agglomeration of dry powder;

[0025] (2) Add the composite adhesive in batches and stir vigorously for 1 to 1.5 hours to form a charcoal paste with uniform plasticity and no dry powder lumps;

[0026] (3) The carbon paste is fed into a hydraulic molding machine and extruded into continuous columnar carbon strips with a diameter of 2.0 to 2.8 mm under a pressure of 10 to 15 MPa. The extrusion speed is controlled at 0.5 to 1.2 m / min.

[0027] Step S4: Step-by-step low-temperature drying and screening of finished product

[0028] (1) The columnar charcoal strips are fed into the rotary kiln for segmented step drying: first, keep at 80℃ for 4 hours, then keep at 110℃ for 4 hours, and finally keep at 130℃ for 2 hours; the maximum temperature throughout the process shall not exceed 130℃.

[0029] (2) The carbon strips collide with each other in the rotary kiln and break into particles naturally. After multi-stage vibrating screening, dust, irregular particles and unqualified materials are removed. Particles with a length of 2-4 mm and an aspect ratio of 1:1.5-1:2 are screened out to obtain the finished product, which is then granulated into columnar activated carbon.

[0030] A highly wear-resistant granulated columnar activated carbon prepared by the above-mentioned preparation process is characterized by: a butane working capacity of 14.8-15.5 g / dl, a wear resistance of 98.5%-99.6%, and a particle cracking deformation rate of <0.8%.

[0031] The present invention has the following beneficial effects:

[0032] 1. This invention utilizes a primary activation followed by low-temperature granulation molding to adapt the silane coupling modification and organic cross-linking bonding system to a low-temperature post-granulation process. The highest drying temperature of the binder system throughout the entire process is only 130℃, ensuring the integrity of the cross-linked structure of silane, polyvinyl alcohol, and lignin without thermal decomposition, thus guaranteeing long-term stable particle bonding strength.

[0033] 2. This invention utilizes modified alkali lignin and low molecular weight urea-formaldehyde resin to construct a bio-organic cross-linking system, eliminating inorganic impurities that clog the micropores of activated carbon. 3-Aminopropyltriethoxysilane builds molecular bridges between the carbon powder and the adhesive layer, significantly enhancing interfacial adhesion. The addition of nano-fumed silica as a pore protectant provides in-situ support between carbon powder particles, preventing the adhesive from encapsulating and blocking the activated carbon micropores. Furthermore, citric acid surface hydroxylation improves adhesive wettability, aminosilane strengthens interfacial adhesion, lignin-urea-formaldehyde resin constructs a flexible three-dimensional cross-linking network, and nano-silica supports the pores, reducing clogging. Ultimately, this achieves a simultaneous improvement in butane adsorption capacity and wear resistance.

[0034] 3. This invention adds a citric acid surface hydroxyl pretreatment process for carbon powder. Through gentle oxidation, a large number of active hydroxyl groups are introduced onto the surface of the activated carbon powder, significantly improving the wettability and interfacial bonding strength between the composite adhesive and the carbon powder. The formed particles are free of microcracks, and their wear resistance effectively exceeds the upper limit. The particle cracking and deformation rate is greatly reduced, and the yield is effectively improved. A water rinsing process is added after pretreatment to avoid residual free acid on the surface, ensuring the stability of the product in application.

[0035] 4. This invention removes free moisture from the particles through a slow, gradient process, avoiding the shrinkage of the adhesive layer and the bending and cracking of the charcoal strips caused by rapid high-temperature dehydration. This significantly improves the dimensional uniformity of the finished product. Combined with natural particle breaking and graded sieving to control the aspect ratio, it ensures uniform filling density and stable airflow distribution in automotive charcoal canisters. Furthermore, all raw materials used in this invention are commercially available conventional industrial products, requiring no additional specialized equipment and allowing for direct modification and implementation on existing activated carbon production lines. The process parameters are all within the standard industrial range, resulting in high operational tolerance and good batch-to-batch product stability. Attached Figure Description

[0036] Figure 1 These are morphological images of the molded activated carbon particles prepared in the embodiments of the present invention. Detailed Implementation

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] Example 1

[0039] Take 20 kg of walnut shell powder and 80 kg of sawdust and put them into a horizontal mixer. Stir at 30 r / min for 30 min until completely mixed. Pass the mixture through a 50 mesh standard vibrating screen, and set aside 100 kg of the sieved mixed wood powder. Take 145 kg of 65 wt% industrial phosphoric acid and add it to the 100 kg mixed wood powder in a kneader. Stir at 60 r / min for 60 min in a constant temperature oil bath at 150℃ until matured, obtaining matured material. Pack the matured material into stainless steel trays, with a material layer thickness of 3 cm, and harden at 190℃ in a hot air oven for 18 h. Send the hardened charcoal to a rotary activation furnace and activate at 460℃ for 4 h with nitrogen. After that, put the activated charcoal into a water washing tank and soak and rinse it in 80℃ hot water for 20 min each time, repeating the rinsing 6 times. The pH of the effluent should be ≥3.5. After rinsing, dry in a hot air oven at 120℃ for 12 h, with a material moisture content of 2.1 wt%. All dried charcoal was fed into a horizontal ball mill and ground with hard steel balls for 2 hours. The output was passed through a 325-mesh sieve, and the activated charcoal powder was collected. All the activated charcoal powder was taken and put into a soaking tank. 200 kg of 0.5 wt% citric acid aqueous solution was prepared and mixed at a solid-liquid ratio of 1:3. The mixture was then soaked at room temperature for 30 minutes. After filtration through a filter screen, the mixture was sprayed with clean water three times. The filter cake was dried in an oven at 80°C for 6 hours to obtain pretreated charcoal powder.

[0040] Prepare the following adhesive raw materials: 5 kg polyvinyl alcohol, 3 kg modified alkali lignin, 2 kg low molecular weight urea-formaldehyde resin, 0.3 kg 3-aminopropyltriethoxysilane, 0.2 kg cocamidopropyl betaine, 0.5 kg nano-fumed silica, and 89 kg deionized water; the modified alkali lignin has a weight-average molecular weight of 10,000 and a phenolic hydroxyl content of 3.5 mmol / g; the urea-formaldehyde resin has a solid content of 50% and a free aldehyde content of 0.25%.

[0041] Add 89 kg of deionized water to the reactor, heat to 88°C, and add 5 kg of polyvinyl alcohol in portions while stirring at 60 rpm. Maintain the temperature and stir for 2 hours until completely dissolved and without clumping. Cool to 70°C, dilute 0.3 kg of 3-aminopropyltriethoxysilane with 0.3 kg of pure water, and add it dropwise into the reactor at a uniform rate over 30 minutes. After the addition is complete, maintain the temperature at 70°C for 1 hour for crosslinking. Separately, take 8.9 kg of warm water, add 0.2 kg of cocamidopropyl betaine and 0.5 kg of nano-fumed silica, and disperse at 1200 rpm for 10 minutes. Add the dispersion, 3 kg of modified alkali lignin, and 2 kg of low molecular weight urea-formaldehyde resin sequentially to the silane base solution, stir at 60 rpm for 30 minutes, and maintain the temperature at 60°C for 1.5 hours for curing. The adhesive should be used within 12 hours of preparation and stored at 32°C.

[0042] 100 kg of pretreated charcoal powder was added to a twin-shaft mixer, and 20 kg of water was added and pre-stirred for 4 minutes. Composite adhesive, equal to 20% of the charcoal powder weight, was added in batches and stirred vigorously for 1.2 hours. The material was manually turned over every 20 minutes to obtain a uniform, plastic charcoal paste. The charcoal paste was fed into a hydraulic extruder with a die diameter of 2.5 mm and a constant pressure of 12 MPa to extrude columnar charcoal strips at a speed of 0.8 m / min. The charcoal strips were laid flat on the rotary kiln mesh belt, with a thickness of 1 cm. Segmented temperature control was applied: first, 80℃ for 4 hours, then 110℃ for 4 hours, and finally 130℃ for 2 hours. The particles were broken down by natural collision within the furnace and passed through 8-mesh, 12-mesh, and 24-mesh vibrating screens. Qualified columnar particles with a length of 2–4 mm and an aspect ratio of 1:2 were collected, which are the finished activated carbon.

[0043] Example 2

[0044] Take 20 kg of walnut shell powder and 80 kg of sawdust and put them into a horizontal mixer. Stir at 30 r / min for 30 min until completely mixed. Pass the mixture through a 40 mesh standard vibrating screen, and set aside 100 kg of the sieved mixed wood powder. Take 140 kg of 65 wt% industrial phosphoric acid and add it to the 100 kg mixed wood powder in a kneader. Stir at 60 r / min for 60 min in a constant temperature oil bath at 150℃ until matured, obtaining matured material. Pack the matured material into stainless steel trays, with a material layer thickness of 3 cm, and harden at 200℃ in a hot air oven for 16 h. Send the hardened charcoal to a rotary activation furnace and activate at 450℃ for 5 h with nitrogen. After that, put the activated charcoal into a water washing tank and soak and rinse in 80℃ hot water for 20 min each time, repeating the rinsing 6 times. The pH of the effluent should be ≥3.5. After rinsing, dry in a hot air oven at 120℃ for 12 h, with a material moisture content of 2.3 wt%. All dried charcoal was fed into a horizontal ball mill and ground with hard steel balls for 2 hours. The output was passed through a 350-mesh sieve, and the activated charcoal powder was collected. All the activated charcoal powder was taken and put into a soaking tank. 200 kg of 0.5 wt% citric acid aqueous solution was prepared and mixed at a solid-liquid ratio of 1:3. The mixture was then soaked at room temperature for 30 minutes. After filtration through a filter screen, the mixture was sprayed with clean water three times. The filter cake was dried in an oven at 80°C for 6 hours to obtain pretreated charcoal powder.

[0045] Prepare the following adhesive raw materials: 3 kg polyvinyl alcohol, 2 kg modified alkali lignin, 1 kg low molecular weight urea-formaldehyde resin, 0.1 kg 3-aminopropyltriethoxysilane, 0.1 kg cocamidopropyl betaine, 0.2 kg nano-fumed silica, and 93.6 kg deionized water; the modified alkali lignin has a weight-average molecular weight of 8000 and a phenolic hydroxyl content of 3.2 mmol / g; the urea-formaldehyde resin has a solid content of 48% and a free aldehyde content of 0.3%; the preparation steps are the same as in Example 1, and the adhesive should be used within 20 hours after preparation and stored at 36°C.

[0046] 100 kg of pretreated charcoal powder was added to a twin-shaft mixer, and 20 kg of water was added and pre-stirred for 3 minutes. Composite adhesive, equal to 20% of the charcoal powder weight, was added in batches and vigorously stirred for 1 hour. The material was manually turned over every 20 minutes to obtain a uniform, plastic charcoal paste. The charcoal paste was fed into a hydraulic extruder with a die diameter of 2.5 mm and a constant pressure of 10 MPa to extrude columnar charcoal strips at a speed of 0.5 m / min. The charcoal strips were laid flat on the rotary kiln mesh belt, with a thickness of 1 cm. Segmented temperature control was applied: first, 80℃ for 4 hours, then 110℃ for 4 hours, and finally 130℃ for 2 hours. The particles were naturally broken down by collision within the furnace and passed through 8-mesh, 12-mesh, and 24-mesh vibrating screens. Qualified columnar particles with a length of 2–4 mm and an aspect ratio of 1:1.5 were collected, which are the finished activated carbon.

[0047] Example 3

[0048] Take 20 kg of walnut shell powder and 80 kg of sawdust and put them into a horizontal mixer. Mix at 30 r / min for 30 min until completely mixed. Pass the mixture through a 60 mesh standard vibrating screen, and keep 100 kg of the sieved mixed wood powder for later use. Take 150 kg of 65 wt% industrial phosphoric acid and add it to the 100 kg mixed wood powder in a kneader. Heat in a 150℃ constant temperature oil bath and stir at 60 r / min for 60 min until matured to obtain matured material. Pack the matured material into stainless steel trays with a material layer thickness of 3 cm and harden in a hot air oven at 180℃ for 20 h. Send the hardened charcoal to a rotary activation furnace and activate at 480℃ for 4 h with nitrogen. Then put the activated charcoal into a water washing tank and soak and rinse in 80℃ hot water for 20 min each time, repeating the rinsing 7 times. The pH of the effluent should be ≥3.5. After rinsing, dry in a 120℃ hot air oven for 12 h, and the material moisture content is 1.9 wt%. All dried charcoal was fed into a horizontal ball mill and ground with hard steel balls for 2 hours. The output was passed through a 400-mesh sieve, and the activated charcoal powder was collected. All the activated charcoal powder was taken and put into a soaking tank. 200 kg of 0.5 wt% citric acid aqueous solution was prepared and mixed at a solid-liquid ratio of 1:3. The mixture was then soaked at room temperature for 30 minutes. After filtration through a filter screen, the mixture was sprayed with clean water three times. The filter cake was dried in an oven at 80°C for 6 hours to obtain pretreated charcoal powder.

[0049] Prepare the following adhesive raw materials: 7 kg polyvinyl alcohol, 4 kg modified alkali lignin, 2 kg low molecular weight urea-formaldehyde resin, 0.5 kg 3-aminopropyltriethoxysilane, 0.3 kg cocamidopropyl betaine, 0.8 kg nano-fumed silica, and 85.4 kg deionized water; the modified alkali lignin has a weight-average molecular weight of 12000 and a phenolic hydroxyl content of 3.8 mmol / g; the urea-formaldehyde resin has a solid content of 52% and a free aldehyde content of 0.2%; the preparation steps are the same as in Example 1, and the adhesive should be used within 8 hours after preparation and stored at 28°C.

[0050] 100 kg of pretreated charcoal powder was added to a twin-shaft mixer, and 20 kg of water was added and pre-stirred for 5 minutes. Composite adhesive, equal to 20% of the charcoal powder weight, was added in batches and vigorously stirred for 1.5 hours. The material was manually turned over every 20 minutes to obtain a uniform, plastic charcoal paste. The charcoal paste was fed into a hydraulic extruder with a die diameter of 2.5 mm and a constant pressure of 15 MPa to extrude columnar charcoal strips at a speed of 1.2 m / min. The charcoal strips were laid flat on the rotary kiln mesh belt, with a thickness of 1 cm. Segmented temperature control was applied: first, 80℃ for 4 hours, then 110℃ for 4 hours, and finally 130℃ for 2 hours. The particles were broken down by natural collision within the furnace and passed through 8-mesh, 12-mesh, and 24-mesh vibrating screens. Qualified columnar particles with a length of 2-4 mm and an aspect ratio of 1:2 were collected, which are the finished activated carbon.

[0051] Comparative Example 1

[0052] Take 20 kg of walnut shell powder and 80 kg of sawdust and put them into a horizontal mixer. Mix at 30 r / min for 30 min until completely mixed. Pass the mixture through a 50 mesh standard vibrating sieve, and keep 100 kg of the sieved mixed wood powder for later use. Take 145 kg of 65 wt% industrial phosphoric acid and add it to the 100 kg mixed wood powder in a kneader. Mix at 60 r / min for 60 min at a constant temperature of 150℃ until matured, and obtain matured material. Pack the matured material into stainless steel trays with a material layer thickness of 3 cm, and harden at a constant temperature of 190℃ in a hot air oven for 18 h. Send the hardened charcoal to a rotary activation furnace and activate at a constant temperature of 460℃ for 5 h with nitrogen. After that, put the activated charcoal into a water washing tank and soak and rinse it in 80℃ hot water for 20 min each time, repeating the rinsing 6 times. The pH of the effluent should be ≥3.5. After rinsing, dry in a hot air oven at 120℃ for 12 h, and the moisture content of the material is 2.1 wt%. All dried charcoal was fed into a horizontal ball mill and ground with hard steel balls for 2 hours. The output was then passed through a 325-mesh sieve to collect the activated charcoal powder. All the activated charcoal powder was taken, and the citric acid soaking pretreatment step was omitted. The charcoal powder was dried and used directly.

[0053] Prepare the adhesive raw materials: Based on 100 kg of carbon powder, prepare 8 kg of polyvinyl alcohol and 92 kg of deionized water, and dissolve them at 88℃ for 2 hours to obtain the adhesive.

[0054] Charcoal powder was premixed with water for 4 minutes, then mixed with polyvinyl alcohol glue for 1.2 hours. The mixture was then extruded into 3mm charcoal strips at 12MPa. Step drying was eliminated; the charcoal was dried at a constant temperature of 120℃ for 12 hours. The charcoal was then naturally broken down and simply sieved, without aspect ratio control.

[0055] Comparative Example 2

[0056] Take 20 kg of walnut shell powder and 80 kg of sawdust and put them into a horizontal mixer. Mix at 30 r / min for 30 min until completely mixed. Pass the mixture through a 50 mesh standard vibrating sieve, and set aside 100 kg of the sieved mixed wood powder. Take 145 kg of 65 wt% industrial phosphoric acid and add it to the 100 kg mixed wood powder in a kneader. Mix at 60 r / min for 60 min at a constant temperature of 150℃ until matured, obtaining matured material. Pack the matured material into stainless steel trays, with a material layer thickness of 3 cm, and harden at a constant temperature of 190℃ in a hot air oven for 18 h. Send the hardened charcoal to a rotary activation furnace and activate at a constant temperature of 460℃ for 5 h with nitrogen. After that, put the activated charcoal into a water washing tank and soak and rinse in 80℃ hot water for 20 min each time, repeating the rinsing 6 times. The pH of the effluent should be ≥3.5. After rinsing, dry in a hot air oven at 120℃ for 12 h, with a material moisture content of 2.1 wt%. All dried charcoal was fed into a horizontal ball mill and ground with hard steel balls for 2 hours. The output was then passed through a 325-mesh sieve to collect the activated charcoal powder. All the activated charcoal powder was taken, and the citric acid soaking pretreatment step was omitted. The charcoal powder was dried and used directly.

[0057] Prepare the adhesive ingredients: Based on 100kg of carbon powder, prepare 5kg of polyvinyl alcohol, 1.5kg of borax, and 93.5kg of deionized water. Heat the polyvinyl alcohol at 88℃, then add the borax and stir until homogeneous to obtain the adhesive.

[0058] 100 kg of pretreated charcoal powder was added to a twin-shaft mixer, and 20 kg of water was added and pre-mixed for 4 minutes. 20% of the charcoal powder's weight in adhesive was added in several batches, and the mixture was vigorously stirred for 1.2 hours. The material was manually turned over every 20 minutes to obtain a uniform, plastic charcoal paste. The charcoal paste was fed into a hydraulic extruder with a die diameter of 2.8 mm and a constant pressure of 12 MPa to extrude columnar charcoal strips at a speed of 0.8 m / min. The charcoal strips were laid flat on the rotary kiln mesh belt, with a thickness of 1 cm. The temperature was controlled in stages: first at 80℃ for 4 hours, then at 110℃ for 4 hours, and finally at 130℃ for 2 hours. The particles were broken down by natural collision within the furnace and passed sequentially through 8-mesh, 12-mesh, and 24-mesh vibrating screens. Qualified columnar particles with a length of 3–4 mm and an aspect ratio of 1:2 were collected to obtain activated carbon.

[0059] Comparative Example 3

[0060] 20 kg of walnut shell powder and 80 kg of sawdust were added to a horizontal mixer and stirred at 30 rpm for 30 minutes to ensure thorough mixing. The mixture was then passed through a 50-mesh standard vibrating sieve, and 100 kg of the mixed wood powder was collected for later use. The mixed wood powder was then loaded into a rotary carbonization furnace, with nitrogen gas purging throughout the process. The temperature was increased to 550°C at a rate of 5°C / min and maintained at this temperature for 30 minutes. After the furnace cooled naturally to below 100°C, the carbonized material was discharged. The carbonized material was then fed into a horizontal ball mill using hard steel balls as the grinding media and ground for 2.5 hours. The material was then discharged, and laser particle size analysis showed an average particle size of approximately 5 μm, yielding carbonized carbon powder, which was sealed and stored for later use.

[0061] The binder is prepared based on 100kg of carbonized carbon powder, and the amounts of each raw material are as follows: 4kg of ultrafine biomass carbon powder, 200kg of deionized water, an appropriate amount of 8% ammonia solution, 1.5kg of 1,2-bis(triethoxysilyl)ethane, 4kg of polyvinyl alcohol, and 30kg of corn starch.

[0062] 4 kg of ultrafine biochar powder and 200 kg of deionized water were added to a stainless steel reactor equipped with ultrasonic function and ultrasonically dispersed for 30 min until no visible agglomerates were observed in the system. Stirring was started at 60 rpm, and 8% ammonia solution was slowly added dropwise, with the pH value monitored in real time and adjusted until it stabilized at 8.2. 1.5 kg of 1,2-bis(triethoxysilyl)ethane was added, and the stirring speed was kept constant. The water bath temperature was raised to 65°C, and the reaction was maintained at this temperature for 5 h. 4 kg of polyvinyl alcohol and 30 kg of corn starch were then added sequentially to the reactor, and the reaction was continued at 65°C with continuous stirring for another 5 h until the system was uniformly viscous and free of dry powder lumps, yielding a silane-modified composite binder. This binder was then sealed and kept at a constant temperature for later use.

[0063] 100 kg of carbonized charcoal powder was added to a twin-shaft mixer, and 30 kg of the aforementioned binder was slowly added in batches. The mixture was stirred continuously at 60 r / min for 1 hour, with the material being turned over every 20 minutes until the mixture was uniformly mixed and possessed uniform plasticity. The mixture was then fed into a hydraulic extrusion molding machine, using a 2.5 mm orifice die and a constant pressure of 11 MPa to extrude continuous columnar charcoal strips. The extrusion speed was stably controlled at 0.8 m / min. The extruded columnar charcoal strips were evenly spread on the drying oven conveyor belt, with a layer thickness of 1 cm. The material was then placed in a hot air circulating oven and dried at a constant temperature of 80℃ for 10 hours. After the moisture content of the material was checked and found to be ≤5 wt%, the material was discharged to obtain shaped charcoal strips. The dried charcoal strips were then loaded into an intermittent steam activation furnace, using saturated steam as the activation atmosphere, and heated to 900℃ at a rate of 8℃ / min, and activated at a constant temperature for 5 hours. After activation and discharge, the carbon particles are transferred to a water washing tank and soaked and rinsed three times in 80℃ hot water to remove surface ash and residual impurities. After rinsing, they are sent to a 120℃ hot air oven to dry for 12 hours. Finally, after multi-stage vibrating sieve screening, particles with a length of 3-5mm are selected as finished products for testing.

[0064] Examples 1-3 and Comparative Examples 1-3 were tested according to ASTM D5228 standard and Daimler Method standard. 1000 finished products were randomly selected, and the percentage of defective particles with through cracks, bending deformation, or edge defects was manually counted by visual inspection. The above test and statistical data are recorded in Table 1:

[0065] Example 1 15.01 99.35 0.6 Example 2 14.82 98.61 0.7 Example 3 15.13 99.52 0.5 Comparative Example 1 13.88 98.41 3.4 Comparative Example 2 14.02 98.15 2.9 Comparative Example 3 12.15 87.30 7.6

[0066] Table 1 Summary of Performance Test Results

[0067] By comparing Examples 1-3 and Comparative Examples 1-3, it can be concluded that:

[0068] 1. The butane working capacity range of the embodiments of the present invention is 14.82-15.13 g / dl, and the optimal embodiment 3 reaches 15.13 g / dl, which is 9% higher than the original basic comparative example 1, 7.91% higher than the borax crosslinked comparative example 2, and 24.5% higher than the comparative example 3, showing significant advantages in adsorption performance.

[0069] The main reason is that this method first completes phosphoric acid activation and fully constructs a hierarchical porous structure before granulation, ensuring the complete development of the original pores of the activated carbon. In contrast, the previous granulation process involves high-temperature activation after molding, which leads to rapid escape of volatiles from the original biomass, easily causing pore collapse, disordered pore size distribution, and severe loss of adsorption pore volume. This invention abandons inorganic crosslinking agents such as borax used in Comparative Example 2, and adopts a pure organic crosslinking system of modified alkali lignin followed by low molecular weight urea-formaldehyde resin, eliminating inorganic salt crystallization residues that block the micropores of activated carbon. Simultaneously, the total amount of binder added is controlled at a low level, preventing excessive filling of carbon powder gaps and pore blockage. Furthermore, nano-fumed silica forms a micro-support structure between carbon powder particles, avoiding large-area coating and blockage of adsorption pores on the carbon powder surface by the adhesive, thus maximizing the preservation of original adsorption pores while improving bonding strength. The granulation matrix is ​​activated carbon powder with all volatiles removed; the low-temperature drying process does not result in a large amount of gas escaping, preventing pore expansion and collapse, and the pore structure stability is far superior to the previous high-temperature activation process for granulated green bodies.

[0070] 2. The wear resistance range of the embodiments of the present invention is 98.61% to 99.52%, and the optimal embodiment 3 reaches 99.52%, which is 1.11 percentage points higher than the original basic comparative example 1, 1.37 percentage points higher than the borax crosslinked comparative example 2, and 12.22 percentage points higher than the comparative example 3. The mechanical strength is significantly improved, which fully meets the wear resistance requirements of long-term bumpy driving in vehicles.

[0071] The main reason is that the highest temperature of the binder in this solution is only 130℃, far lower than the thermal decomposition temperature of polyvinyl alcohol, silane, and lignin, ensuring the integrity of the cross-linked network structure. In contrast, Comparative Example 3 requires activation at 900℃, resulting in almost complete pyrolysis and carbonization of the organic binder components, essentially eliminating the bonding effect. The final strength relies solely on the sintering of the carbon skeleton, leading to extremely poor wear resistance. The gentle oxidation of citric acid introduces a large number of active hydroxyl groups onto the carbon powder surface, eliminating its hydrophobic inertness and allowing the adhesive to fully wet the carbon powder particles, resulting in a much stronger interfacial bond than physical coating. The original single polyvinyl alcohol solution lacked surface modification, making the adhesive layer and carbon powder interface easily peel off, which is the core reason for its low upper strength limit.

[0072] Furthermore, one end of the KH-550 silane forms a chemical bond with the hydroxyl groups on the surface of the carbon powder, while the other end undergoes a cross-linking reaction with polyvinyl alcohol and lignin organic chains, building covalent molecular bridges between the inorganic carbon powder and the organic adhesive layer. The interfacial bonding strength is far higher than that of simple physical adhesion. The modified alkali lignin and urea-formaldehyde resin are combined to form a three-dimensional cross-linked network that combines rigidity and toughness. The shear resistance and friction resistance of the adhesive layer are far higher than that of the linear adhesive structure of single polyvinyl alcohol. Under external friction, the adhesive layer is less likely to peel off or the particles will fall off.

[0073] 3. The particle cracking deformation rate in the embodiments of the present invention is less than 0.8%, and the optimal embodiment 3 is only 0.5%, which is 85.3% lower than the original basic comparative example 1, 82.8% lower than the borax crosslinking comparative example 2, and 93.4% lower than the comparative example 3. The uniformity of finished product size and the pass rate are greatly improved.

[0074] The main reason is that the raw material in the previous granulation process contains a large amount of virgin wood components. During high-temperature activation, hydrogen and oxygen elements rapidly release a large amount of volatiles, which, combined with the intense thermal expansion and contraction, generates concentrated internal stress, which is the core reason for particle cracking and deformation. This solution uses activated carbon powder with completely removed volatiles as the matrix, and subsequent drying is only at low temperature. There is no large amount of gas escape and no intense thermal expansion and contraction, thus avoiding shrinkage cracking from a mechanistic perspective. Step-drying slowly dehydrates to avoid internal stress, and the free water inside the particles is slowly and evenly removed, while the adhesive layer simultaneously and slowly solidifies and shrinks. In contrast, single constant-temperature rapid drying easily causes the surface adhesive layer to solidify first, followed by the evaporation of internal water, which cracks the particles. At the same time, the rapid shrinkage of the adhesive layer easily causes bending deformation. In addition, the carbon powder surface is treated with hydroxylation and pre-dispersion of adhesive solution, so that the binder is highly uniformly distributed in the carbon paste. The formed particles have no local weak bonding areas, and cracks will not initiate at weak points when subjected to drying stress, resulting in better overall structural consistency.

[0075] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A process for preparing highly wear-resistant granulated columnar activated carbon, characterized in that, Includes the following steps: Step S1: Preparation of wood-based activated carbon powder by phosphoric acid activation: (1) Raw material mixing: Walnut shell powder and sawdust are mixed at a mass ratio of 0.2:0.8 and sieved through a 40-60 mesh screen; phosphoric acid aqueous solution and mixed wood powder are mixed at a mass ratio of 1.4-1.5:1 and aged at a constant temperature of 150℃ for 60 minutes to obtain aging material; (2) Hardening and shaping: The calcined material is placed in an environment of 180-200℃ for 16-20 hours to harden; (3) Inert atmosphere activation: Hardened carbon is activated at 450-480℃ for 0.5-1h under nitrogen atmosphere; (4) Washing and drying: Rinse the activated carbon until pH=6, then dry at 120℃; (5) Ball milling: Dry carbon is ball milled to 325-400 mesh to obtain activated carbon powder; (6) Pretreatment of hydroxyl groups on the surface of carbon powder: Activated carbon powder is immersed in a 0.5% citric acid aqueous solution at room temperature for 30 min, rinsed with water to remove free acid on the surface, and then dried at 80℃; Step S2: Preparation of silane-modified lignin composite adhesive: Based on the total mass of activated carbon powder, the adhesive contains the following components: 3%–7% polyvinyl alcohol, 2%–4% modified alkali lignin, 1%–2% low molecular weight urea-formaldehyde resin, 0.1%–0.5% 3-aminopropyltriethoxysilane, 0.1%–0.3% cocamidopropyl betaine, 0.2%–0.8% nano-fumed silica, with the balance being deionized water; Step S3: Mixing and Hydraulic Extrusion Molding Pre-treated activated carbon powder is pre-stirred with water for 3-5 minutes, then mixed with composite adhesive for 1-1.5 hours to obtain plastic carbon paste. The paste is then extruded into columnar carbon strips with a diameter of 2.3-2.7 mm using a pressure of 10-15 MPa. Step S4: Stepped low-temperature drying and screening: The columnar carbon strips are dried in stages: first, they are kept at 80℃ for 4 hours, then at 110℃ for 4 hours, and finally at 130℃ for 2 hours. After the carbon strips are naturally broken into particles in the furnace, they are screened in multiple stages to obtain the finished product, which is then granulated into columnar activated carbon.

2. The preparation process according to claim 1, characterized in that, The preparation steps of the adhesive solution include: heating to 85-90℃ to dissolve polyvinyl alcohol, cooling to 70℃ and adding 3-aminopropyltriethoxysilane dropwise for crosslinking reaction for 1 hour; nano-fumed silica is pre-dispersed with some water and cocamidopropyl betaine at high speed to form a dispersion; then the dispersion, modified alkali lignin, and low molecular weight urea-formaldehyde resin are added sequentially, and the mixture is kept at 60℃ for 1.5 hours for curing.

3. The preparation process according to claim 1, characterized in that, The modified alkali lignin in step S2 has a weight-average molecular weight of 8000-12000 and a phenolic hydroxyl content of ≥3.2mmol / g; the low molecular weight urea-formaldehyde resin has a solid content of 48%-52% and a free aldehyde content of ≤0.3%.

4. The preparation process according to claim 1, characterized in that, In step S1, the nitrogen flow rate is controlled at 0.8–1.5 m³ / h per 100 kg of hardened carbon; in step S3, the extrusion speed is controlled at 0.5–1.2 m / min.

5. The preparation process according to claim 1, characterized in that, The finished columnar activated carbon obtained after sieving in step S4 has a length of 2-4 mm and an aspect ratio of 1:1.5-1:

2.

6. A post-granulated columnar activated carbon prepared by the preparation process according to any one of claims 1-5, characterized in that, The wear resistance of activated carbon is 98.5% to 99.6%, and the particle cracking deformation rate is <0.8%.